Atrophic gastritis and Helicobacter pylori infection in outpatients referred for gastroscopy. Issue 4 (1st April 2000) - Oksanen, A; Sipponen, P; Karttunen, R; Miettinen, A; Veijola, L; Sarna, S; Rautelin, H
Abstract : BACKGROUND: Atrophic gastritis has been shown to be one of the long term sequelae of Helicobacter pylori infection. AIMS: To determine the prevalence of atrophic gastritis in outpatients, to study the accuracy of serological methods for revealing atrophy, and to define the association of H pylori infection with atrophic gastritis in these patients. PATIENTS/METHODS: A total of 207 consecutive outpatients referred for gastroscopy were included. Biopsy specimens from the antrum and corpus were assessed histologically according to the Sydney system. Serum samples were studied for H pylori IgG and IgA antibodies by enzyme immunoassay, CagA antibodies by immunoblot, pepsinogen I by an immunoenzymometric assay, gastrin by radioimmunoassay, and parietal cell antibodies by indirect immunofluorescence. RESULTS: Histological examination revealed atrophic gastritis in 52 (25%) of 207 patients. H pylori and CagA antibodies were strongly associated with atrophic antral gastritis but poorly associated with atrophic corpus gastritis. Low serum pepsinogen I was the most sensitive and specific indicator of moderate and severe atrophic corpus gastritis. All six patients with moderate atrophic corpus gastritis had H pylori infection but eight of 10 patients with severe atrophic corpus had increased parietal cell antibodies and nine had no signs of H pylori infection. CONCLUSIONS: Atrophic antral gastritis was strongly associated with CagA positive H pylori infection. Severe atrophic corpus gastritis was not determined by H pylori tests but low serum pepsinogen I, high gastrin, and parietal cell antibodies may be valuable in detecting these changes.